2010
DOI: 10.1097/opx.0b013e3181ea19c7
|View full text |Cite
|
Sign up to set email alerts
|

Spectacle Lenses Designed to Reduce Progression of Myopia: 12-Month Results

Abstract: Purpose To report the results of 12-month wear of three novel spectacle lens designs intended to reduce peripheral hyperopic defocus and one standard design control lens and their effect on the progression of myopia in Chinese children aged 6 to 16 years. Methods Chinese children (n = 210) with myopia (−0.75 D to −3.50 D sphere, cylinder ≤−1.50 D) were randomized to one of four groups wearing either one of three novel spectacle lens designs (types I, II, or III) or conventional, single-vision spectacle lense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
186
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(210 citation statements)
references
References 24 publications
3
186
1
9
Order By: Relevance
“…29 These devices are still not widely available, and are quite expensive compared to conventional glasses. Though not at present appropriate for large-scale treatment programs, they may eventually offer an even greater vision protection benefit.…”
Section: Results From Itt Analysis In This Randomized Trialmentioning
confidence: 99%
“…29 These devices are still not widely available, and are quite expensive compared to conventional glasses. Though not at present appropriate for large-scale treatment programs, they may eventually offer an even greater vision protection benefit.…”
Section: Results From Itt Analysis In This Randomized Trialmentioning
confidence: 99%
“…The potential link between peripheral refraction and refractive error in these studies has led to experiments in which spectacle lenses or contact lenses alter the peripheral refraction. [25][26][27] It has been found that such lenses may reduce myopia progression over a 1-year period in some studies. 26 The Cambridge Anti-Myopia Study (CAMS) is designed to evaluate a dual treatment modality for myopia on myopia progression rates.…”
Section: Discussionmentioning
confidence: 99%
“…These optical strategies appear to slow the progression of myopia by B30-55% and without adverse effects. [38][39][40][41][42] It has been suggested that reducing the progression of myopia by as little as 33% would reduce the number of highly myopic eyes (4 À 5.00 D) by as many as 75%. 43 Data from a longer term clinical study, involving the use of contact lenses to reduce the hyperopic defocus at the peripheral retina, showed that the ability of these lenses to slow the progression of myopia was a consistent 40% per year over the study period of 43 months.…”
Section: Optical Interventionmentioning
confidence: 99%